2022
DOI: 10.1038/s41598-022-17338-1
|View full text |Cite
|
Sign up to set email alerts
|

A GLP1 receptor agonist diabetes drug ameliorates neurodegeneration in a mouse model of infantile neurometabolic disease

Abstract: Infantile neuroaxonal dystrophy (INAD) is a rare paediatric neurodegenerative condition caused by mutations in the PLA2G6 gene, which is also the causative gene for PARK14-linked young adult-onset dystonia parkinsonism. INAD patients usually die within their first decade of life, and there are currently no effective treatments available. GLP1 receptor (GLP-1R) agonists are licensed for treating type 2 diabetes mellitus but have also demonstrated neuroprotective properties in a clinical trial for Parkinson’s di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…The effects of semaglutide during the juvenile period have been poorly investigated in rodents. Indeed, to our knowledge only one study probed the effects of semaglutide after weaning, in a model of infantile neuroaxonal dystrophy, and did not report any interference of semaglutide with the growth of chow diet-fed mice [49]. This is consistent with our data in CD mice.…”
Section: Chronic Semaglutide Treatment Further Compromises Linear Gro...supporting
confidence: 91%
“…The effects of semaglutide during the juvenile period have been poorly investigated in rodents. Indeed, to our knowledge only one study probed the effects of semaglutide after weaning, in a model of infantile neuroaxonal dystrophy, and did not report any interference of semaglutide with the growth of chow diet-fed mice [49]. This is consistent with our data in CD mice.…”
Section: Chronic Semaglutide Treatment Further Compromises Linear Gro...supporting
confidence: 91%
“…The main mechanism of action of these GLP-1RA is the stimulation of the GLP-1R that triggers the activation of several metabolic pathways involved in insulin secretion, lipid metabolism, energy expenditure, pro-survival and anti-apoptotic cellular signaling, and oxidative stress prevention, in several tissues like the pancreas, central nervous system, heart, muscle, kidneys, gut, among others ( 15 ). The wide distribution of the GLP-1R has allowed the study of semaglutide and liraglutide pharmacological protocols to improve metabolic diseases in several experimental models ( 26 , 40 , 48–50 ). The assessment of these GLP-1RA could elucidate the role of these drugs in the cellular signaling process of obese-related diseases, which could support the development of new pharmacological approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these GLP-1RA medications have also been related to a reduction of neuroinflammation, probably due to its possible role in neuronal insulin signaling pathway restoration ( 49 , 67 , 68 ). Hence, semaglutide and liraglutide could also have the potential to ameliorate neurodegeneration processes observed in pathologies like Alzheimer’s and Parkinson’s diseases, although further research is needed ( 48 , 69 ). Moreover, clinical trials have reported a reduction of the inflammatory C-reactive protein ( 70 ), which could indicate that this drug may also regulate the immune system, although this approach requires further assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with SEM improved neurodegeneration, especially in the ventral posterior medial and lateral nuclei of the thalamus (VPM/VPL) in Pla2g6−/− mice [ 97 ].…”
Section: Sem Potential Mechanism Of Action In Pdmentioning
confidence: 99%